(untitled) (The Pakistan Development Review, 2006)
Australia is highly dependent on its natural resources; therefore it needs to develop a national accounting system whereby the concept of natural resource asset depletion is incorporated into its national income accounts. The present study suggests that if the national income accounting system of the economy is deficient in highlighting the gap in estimated income and sustainable income, then such a system needs to be improved [Ahmed and Mallick (1997)]. In a previous analysis of the Australian economy [Mallick, Sinden, and Thampapillai (2000)], showed that reconciliation between the goals of sustainability and employment may be achieved by a real wage reduction of approximately 8-10 percent. The analysis was structured within the framework of a simple Keynesian model of income determination and a Cobb-Douglas production function.